Empyema necessitatis due to Pseudomonas aeruginosa in a child with cerebral palsy. Issue 1 (January 2020) - Nishimura, Akihiro; Yamaguchi, Hiroshi; Ito, Yusuke; Tokumoto, Shoichi; Toyoshima, Daisaku; Kasai, Masashi; Maruyama, Azusa
Abstract: Empyema necessitatis (EN) is a rare complication of empyema in which the pleural infection spreads outside the pleural space. Lower airway infections are common among children with cerebral palsy (CP). Although harmless to healthy individuals, Pseudomonas aeruginosa can cause invasive infections, including CP, in immunocompromised hosts. Mycobacterium tuberculosis and Actinomyces spp. have been reported as common causative organisms of EN. However, EN caused by P. aeruginosa has never been reported. We report the case of an 8-year-old girl with CP without tracheotomy who was admitted to our hospital with complaints of fever and increased epileptic seizures. First, she was diagnosed with pneumonia and treated with antibiotics. However, seven days after admission, a palpable mobile mass overlying the lower part of the shoulder blade was noticed. Enhanced magnetic resonance imaging revealed broad high signal area on T2-weighted and diffusion-weighted images, indicating empyema of the left lower lung that had penetrated the pleural wall and spread to the subcutaneous area of the left back. Thus, she was diagnosed with EN. Twelve days after admission, P. aeruginosa was detected from the pus culture. Patients with CP who have chronic lung diseases, such as pneumonia, atelectasis, or empyema, may need careful follow up.